1985
DOI: 10.2527/jas1985.602480x
|View full text |Cite
|
Sign up to set email alerts
|

Threonine Requirement of Pigs Weighing 5 to 15 kg and the Effect of Excess Methionine in Diets Marginal in Threonine

Abstract: Experiments were conducted to estimate the threonine requirement of pigs weighing 5 to 15 kg and to determine whether excess methionine increased the threonine requirement. Feeding .70% dietary threonine in Exp. 1 maximized (P less than .01) gain/feed and minimized (P less than .01) plasma urea N. Plasma threonine was increased (P less than .01) by threonine supplementation and the rate of increase accelerated above .65% dietary threonine. Threonine supplementation did not affect plasma methionine, tryptophan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
1
5

Year Published

1989
1989
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 11 publications
4
12
1
5
Order By: Relevance
“…The lower serum urea nitrogen concentration in the piglets fed the low protein, AA-supplemented diets is indicative of a reduction of the AA in excess in these diets, and is probably depending more on the amounts and balance of AA available systemically (Shriver et al, 2003). Rosell and Zimmerman (1985) reported that plasma urea declined at the estimated requirement for AA, reflecting maximum efficiency of nitrogen utilization and minimum synthesis of urea at that point. Therefore, dietary nitrogen from diets with a reduced CP level, but balanced for AA, may be used more efficiently.…”
Section: Discussionmentioning
confidence: 97%
“…The lower serum urea nitrogen concentration in the piglets fed the low protein, AA-supplemented diets is indicative of a reduction of the AA in excess in these diets, and is probably depending more on the amounts and balance of AA available systemically (Shriver et al, 2003). Rosell and Zimmerman (1985) reported that plasma urea declined at the estimated requirement for AA, reflecting maximum efficiency of nitrogen utilization and minimum synthesis of urea at that point. Therefore, dietary nitrogen from diets with a reduced CP level, but balanced for AA, may be used more efficiently.…”
Section: Discussionmentioning
confidence: 97%
“…In young growing pigs, 1.63 % dietary arginine had no effect on growth and feed intake and only affected feed efficiency, when lysine was marginally deficient (1.03 % Lys; Hagemeier et al, 1983). In other studies with piglets, 0.67, 1.6 and 2.0 % supplemental arginine decreased weight gain and feed intake, but had variable effects on gain/feed and no effect on the N-balance (Southern and Baker, 1982;Anderson et al, 1984), whereas a moderate arginine supplementation (0.22 %) did not affect performance of growing piglets (Rosell and Zimmerman, 1985). From experiment I on sows (3 % supplemental arginine from day 14 until day 31 of pregnancy and from day 105 until farrowing), a high tolerance could be concluded as well as from the subchronic study in rats (5 % arginine for 13 weeks) 9 .…”
Section: Safety For the Target Animalmentioning
confidence: 80%
“…ROSELL & ZIMMERMAN (1985), trabalhando com leitões dos 5 aos 15kg, e BERTO et al (2002), com leitões dos 7 aos 12kg, avaliaram o desempenho e o teor plasmático de uréia, recomendando a relação lisina:treonina total de 100:61. ZHANG et al (1984), avaliando o valor biológico da proteína, para leitões desmamados com três semanas de idade, também concluíram que a relação lisina:treonina total para ótima utilização de nitrogênio foi de 100:61.…”
Section: Resultsunclassified